Digital rights management and watermarking of multimedia content for m-commerce applications. - Hartung, F. (IEEE Communications magazine)
E-commerce has become a huge business and a driving factor in the development of the Internet. Online shopping services are well established and will, with the advent of evolved 2G and 3G mobile networks, soon be complemented by their wireless counterparts. Furthermore, online delivery of digital media, such as MP3 audio or video, is very popular today and will become an increasingly important part of e-commerce and mobile e-commerce (m-commerce). However, a major obstacle for digital media distribution and associated business is the possibility of unlimited consecutive copying in the digital domain, which threatens intellectual property rights (e.g., copyrights). Digital rights management systems are required to protect rights and business. DRM systems typically incorporate encryption, conditional access, copy control mechanisms, and media identification and tracing mechanisms. Watermarking is the technology used for copy control and media identification and tracing. Most proposed watermarking methods use a so-called spread spectrum approach: a pseudo-noise signal with small amplitude is added to the host signal, and later on detected using correlation methods. A secret key is used to ensure that the watermark can only be detected and removed by authorized parties. Thus, watermarking is an essential component of modern DRM systems. Several standardization bodies are involved in DRM standardization. Some examples, (MPEG-4, SDMI, and DVD), are discussed in this article. Watermarking as an enabling technology is especially highlighted. Furthermore, the relation between DRM and m-commerce, and the impact on business models for m-commerce are discussed. A common experience today is that Internet e-commerce applications cannot always easily be adapted for mobile telecommunications systems. We emphasize, however, that DRM and watermarking can benefit from the additional information available in mobile telecommunications systems, and can thus help to improve rights management for digital media delivery.